Empowerment Public DTW Bantimurung Based Language English in Bantimurung District, Maros Regency, South Sulawesi - Dwi Septiwiharti; Yoel Octobe Purba; Anwar Sadat; Zakir Hossen Shaikh; Dina Mardina (Marsiurupan: Journal of Community Development and Empowerment, 2026)
Bantimurung Tourism Park is part of the Bantimurung Bulusaraung National Park area located in Bantimurung District, Maros Regency, South Sulawesi. With the English skills of the local community, they will be able to develop various multidisciplinary business opportunities based on the interests and needs of visitors. Considering the existing potential and problems faced by some residents of tourist areas, partnerships with related institutions are needed. Universities, as organizers of the Tri Dharma of Higher Education, especially the Community Service Program (KKN), will continue to synergize in developing the region. The KKN-PPM program will significantly encourage economic growth in the community through entrepreneurship. English-based social. Participatory methods involving community groups, it will be easier for the community to accept the programs offered in an applicable manner. The objectives of the KKN-PPM implementation are: 1) Establishing local groups. Tourist Guide who will guide every tourist who comes. 2) The formation of business groups aimed at changing the mindset of the community, who are not just spectators of every tourist who comes, but will give birth to an English-based community business. 3) The establishment of English language schools and English language villages with the English Home model (GAU ASE, 2013).